2018
DOI: 10.1080/10717544.2018.1447049
|View full text |Cite
|
Sign up to set email alerts
|

On-target and direct modulation of alloreactive T cells by a nanoparticle carrying MHC alloantigen, regulatory molecules and CD47 in a murine model of alloskin transplantation

Abstract: Biomimetic nanoparticles have been reported as immune modulators in autoimmune diseases and allograft rejections by numerous researchers. However, most of the therapeutics carrying antigens, toxins or cytokines underlay the mechanism of antigen presentation by cellular uptake of NPs through pinocytosis and phagocytosis. Few researches focus on the direct and antigen-specific modulation on T cells by NPs and combined use of multiple regulatory molecules. Here, polylactic-co-glycolic acid nanoparticles (PLGA-NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Finally, a model of allotransplantation received polyethyleneimine (PEI)-poly lactic-co-glycolic acid (PLGA) nanoparticles functionalized with an allogeneic MHC-mimic, CD47, and immunosuppressants (IS), that triggered peripheral deletion of MHC-alloreactive T cells and promoted Treg expansion. Adapted from references [8,67,71,72,74,[76][77][78]82]. tolerogenic DCs achieved 300 days of IS-free survival after transplantation with MHCmismatched livers.…”
Section: Tolerogenic Cells Tolerogenic Leucocytesmentioning
confidence: 99%
“…Finally, a model of allotransplantation received polyethyleneimine (PEI)-poly lactic-co-glycolic acid (PLGA) nanoparticles functionalized with an allogeneic MHC-mimic, CD47, and immunosuppressants (IS), that triggered peripheral deletion of MHC-alloreactive T cells and promoted Treg expansion. Adapted from references [8,67,71,72,74,[76][77][78]82]. tolerogenic DCs achieved 300 days of IS-free survival after transplantation with MHCmismatched livers.…”
Section: Tolerogenic Cells Tolerogenic Leucocytesmentioning
confidence: 99%
“…A simpler approach of conjugating CD47-Fc to the particle surface has been explored by Wan et. al and Shahzad et al in response to the recent finding that CD47-Fc can act as a self-marker and prevent macrophage uptake in aAPCs 109,117,118 although this approach lacks T-Cell specificity and does not classically present antigen on MHC 109,118 . Lastly, there are some strategies that aim to create antigen specificity by encapsulating antigen within particles and using coupled targeting ligands to release antigen to the T-Cell in a controlled manner.…”
Section: T-cellsmentioning
confidence: 99%
“…The major tolerogenic cytokines are TGF-β, IL-10, and IL-2, although the effectiveness of IL-2 at inducing tolerance depends on the environment, as it can also expand effector T-Cells if in the presence of activating costimulatory signals 119,122 . Since there is no cell binding component, delivery methods are restricted to nanoparticles ranging from 100–300nm with particle materials including PLGA 118,123 , cyclodextrin nanogels 121 , and liposomes 124 . Currently all targeted T-Cell drug delivery for tolerance induction is directed at CD4+ T-Cells for the induction of FOXP3+ regulatory T-Cells through incorporation of an anti-CD4 surface ligand, although there is potential for expansion to other T-Cell types.…”
Section: T-cellsmentioning
confidence: 99%
“…Furthermore, combining the NP treatment with a short course of rapamycin results in a significant synergy in terms of the prolongation of islet allograft survival. 56 In another study, Shahzad et al 57 developed PLGA NPs conjugated with H-2K b -Ig dimer, CD47-Fc, and PD-L1-Fc, with encapsulated recombinant TGF-β, to specifically target and silence antigen-specific CD8 T cells. The authors applied this formulation in a single MHC-mismatched murine model of skin transplantation and demonstrated that three injections of this formulation on days 9, 11, and 13 post-transplant significantly reduced the numbers of antigen-specific CD8 T cells in the graft, blood, and spleen by inducing their apoptosis; consequently, the survival of the skin allograft was significantly prolonged.…”
Section: Nanotechnology For Promoting Long-term Transplant Survivalmentioning
confidence: 99%
“…The authors applied this formulation in a single MHC-mismatched murine model of skin transplantation and demonstrated that three injections of this formulation on days 9, 11, and 13 post-transplant significantly reduced the numbers of antigen-specific CD8 T cells in the graft, blood, and spleen by inducing their apoptosis; consequently, the survival of the skin allograft was significantly prolonged. 57 Currently, the only experimental protocols that have successfully achieved transplantation tolerance in human kidney recipients require donor bone marrow transplantation (BMT) and the induction of recipient mixed chimerism. [58][59][60] Using a minor histocompatibility antigen (Hy)-mismatched C57BL/6 model of BMT, Hlavaty et al 61 tested the efficacy of a nanoparticle-based approach for the induction of mixed chimerism.…”
Section: Nanotechnology For Promoting Long-term Transplant Survivalmentioning
confidence: 99%